1992
DOI: 10.3109/10428199209061558
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Prognostic Index for Clinical use in Identification of Poor-Risk Patients with Hodgkin's Disease at Diagnosis

Abstract: The aim of this study was to assess the feasibility of using objective data obtained at the time of diagnosis of Hodgkin's disease to predict those patients who were likely to die of progressive disease within four years. Ninety-two consecutive patients from one centre (Newcastle upon Tyne) were used to construct a numerical index based on disease stage (Ann Arbor), age, haemoglobin and absolute lymphocyte count. Weight was assigned according to a predictive value from univariate and multivariate analyses base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Our study suggests that results of treatment in the older patient with HD have not improved since the studies first published in the 1980s (Kennedy et al, 1985). Improvements in treatment outcomes in younger patients have been due to the introduction of more intensive regimens (Proctor et al, 1992;Bartlett et al, 1995;Diehl et al, 1998) but these are poorly tolerated in older patients, even among those initially considered fit enough to undergo intensive treatment. In an effort to improve results by minimizing toxicity, specific regimens for the elderly have been introduced; CVP/ CEB (cyclophosphamide, vincristine, prednisone/carboplatin, etoposide, bleomycin) (Levis et al, 1996) was found to be well tolerated but, unfortunately, the relapse rate was high, a pattern similar to that seen in our small cohort of patients treated within the Scotland and Newcastle Lymphoma Group with PCOME (Table IV; data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…Our study suggests that results of treatment in the older patient with HD have not improved since the studies first published in the 1980s (Kennedy et al, 1985). Improvements in treatment outcomes in younger patients have been due to the introduction of more intensive regimens (Proctor et al, 1992;Bartlett et al, 1995;Diehl et al, 1998) but these are poorly tolerated in older patients, even among those initially considered fit enough to undergo intensive treatment. In an effort to improve results by minimizing toxicity, specific regimens for the elderly have been introduced; CVP/ CEB (cyclophosphamide, vincristine, prednisone/carboplatin, etoposide, bleomycin) (Levis et al, 1996) was found to be well tolerated but, unfortunately, the relapse rate was high, a pattern similar to that seen in our small cohort of patients treated within the Scotland and Newcastle Lymphoma Group with PCOME (Table IV; data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…Over the years, several groups have described prognostic scores and used these factors to tailor treatment [17,18]. At present, treatment is adjusted for patients who are classified into different prognostic groups based on a combination of clinical, biological, and pathological characteristics and extensive staging procedures.…”
Section: Present-day Hlmentioning
confidence: 99%
“…Consequently, therapeutic strategies are tailored according to initial prognostic factors. All prognostic scores established for Hodgkin disease take into account either the presence of stage IV disease or the number of extranodal sites (1)(2)(3). Therapeutic groups are determined according to biologic factors (eg, anemia, lymphopenia) and the extent of disease (eg, number of lymph nodes or presence of bulky tumor, extranodal involvement, stage IV disease).…”
Section: Prognosis and Therapymentioning
confidence: 99%